2013
DOI: 10.1177/0892705712470264
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PTFE on the mechanical, friction, and wear properties of CF/PMMA composites

Abstract: The effects of polytetrafluoroethylene (PTFE) on the tensile and tribological properties of carbon fiber-reinforced poly(methyl methacrylate) (PMMA) composites were studied. Tribological tests were conducted on an Amsler friction and wear tester using a block-on-ring arrangement. It was observed that the PTFE played a main role in the tensile-resistant and wear-resistant properties of the PMMA composites. The tensile properties were ruled by the fiber-matrix adhesion. And the excellent tribological performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Many researchers have studied the friction and wear behavior of PTFE-filled polymers. [13][14][15][16] It has been reported that high-sliding velocity and loads promote the formation of a compact transfer film at the early stage of contact. This film formation is believed to be the predominant mechanism giving rise to excellent wearresistant performance of the solid lubricants with high load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the friction and wear behavior of PTFE-filled polymers. [13][14][15][16] It has been reported that high-sliding velocity and loads promote the formation of a compact transfer film at the early stage of contact. This film formation is believed to be the predominant mechanism giving rise to excellent wearresistant performance of the solid lubricants with high load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [15] found that the friction coefficient and wear rate of poly(phthalazinone ether sulfone ketone) (PPESK) composite filled with PTFE decreased substantially compared with the neat PPESK. For the carbon fiber (CF)/PMMA composites prepared by physical extrusion, filling PTFE can further reduce friction and wear [16]. The addition of PTFE in polymer matrix helped in the formation of a continuous and uniform transfer film and resulted in a reduction in the friction coefficient [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…1,[21][22][23] PTFE composite materials are generally prepared by simple dry blending or coating fillers with PTFE. 24 However, such methods lead to inhomogeneous distribution of fillers within PTFE and causes undesirable effect on the properties of PTFE composite membranes. In this regard, aggregation of colloidal particles has gained a large interest and has been employed in the fabrication of PTFE composite particles.…”
Section: Introductionmentioning
confidence: 99%